Narrativas infantiles respecto de los cambios familiares, a partir de las áreas de desarrollo afectiva, social, comportamental y académica de tres niños de 11 y 12 años (2024)
This degree work presents qualitative research into the narratives of 3 children between the ages of eight and twelve, who belong to reconstituted families. From a deep interview it is intended to understand how the child builds his observations of affiliation, interaction with other subsystems, those related to the family as a unit of control and the development of their learning; when their go through a process of dissolution and subsequent reconstruction of their new family nucleus. This is based on Bronfenbrenner's ecological theory